Pengaruh Kedisiplinan Dan Sikap Mandiri Terhadap Minat Berwirausaha Pada Siswa SMK Di Kota Bogor - Sutina Sutina; Toto Widiarto (Jurnal Ilmiah Wahana Pendidikan, 2020)
The habit of independent attitude and discipline still needs to be improved among SMK students. Real discipline that can be applied in the field of entrepreneurship. Discipline in schools needs special attention, because discipline can affect students' interest in learning, especially entrepreneurial interest that can be influenced by other variables, such as independent attitude. The purpose of this research is to look for the influence of discipline and independent attitude on student entrepreneurial interest together, the effect of discipline on entrepreneurial interest, and the effect of independent attitude on entrepreneurial interest. The discipline used is quantitative discipline, assisted by the SPSS 22 program. The classic test used is the normality test and Linearity test and coofesien. The results of the study showed that there was a significant influence of discipline and independent attitude on entrepreneurial interest, there was no effect of independent attitude on entrepreneurial interest and there was a influence on discipline on entrepreneurial interest.